The take-up of Carer's Allowance: A feasibility study - Richard Berthoud (University of Essex, Institute for Social and Economic Research (ISER), 2010)
The Department for Work and Pensions committed itself to exploring the take-up of Carer's Allowance at the House of Commons Public Accounts Committee in May 2009. This study was commissioned as a first step in that enquiry. The report summarises the questions and discusses possible research approaches, with a view to considering more detailed investigations. In-depth analysis of the Family Resources Survey (FRS) and a review of previous research and current statistics helped to formulate the study conclusions.
Keywords: H55; I38; 330; Carers Allowance; Take-up; Family Resources Survey; Meinungsforschung; Soziale Lage; Familie; Statistische Methode; Großbritannien